The beauty of Allah's creation - Omer, Spahic (www.islamicity.org, 2019)
The Prophet (pbuh) has said that Allah is beautiful and He loves beauty. It is for this that the whole of Allah’s creation has been designed and created according to the highest heavenly standard of splendor and order impossible to be ever emulated by anyone. According to Ibn al-‘Arabi, who epitomized the Sufi speculative ontological thought, the divine beauty through which God is named “Beautiful”, and by which He described Himself as loving beauty, is in all things. There is nothing in existence but beauty, for God created the cosmos only in His image, that is, in the image of His infinite beauty. Hence all cosmos with all its objects and events is beautiful.